ANALISIS PENGARUH HARGA, KARAKTERISTIK PRODUK, PROMOSI DAN KESADARAN AKAN MEREK TERHADAP INTENSI PEMBELIAN MOTHERBOARD - Lesmana, Andreas; Adhinugraha, Daniel (Journal of Business Strategy and Execution, 2014)
The main objective of this study was to analyze the effect of pricing, product characteristics, promotion and brand awareness of intentions to purchase motherboard. This study used questionnaires and interviews to obtain data to be analyzed. The number of respondents was 271 respondents and scattered in several major cities in Indonesia. Data gathered was analyzed using SPSS Statistics 21. The result fo this study showed, (1) There is no positive influence of the price on purchase intentions, (2) Characteristics of the product do not have positive influence on purchase intentions, (3) There is no positive influence of Awareness of the brand on purchase intentions. (4) Promotion has positive influence on purchase intentions.